Dynamic debonding in layered structures: a coupled ALE-cohesive approach (Fracture and Structural Integrity, 2017)
A computational formulation able to simulate crack initiation and growth in layered structural systems is proposed. In order to identify the position of the onset interfacial defects and their dynamic debonding mechanisms, a moving mesh strategy, based on Arbitrary Lagrangian-Eulerian (ALE) approach, is combined with a cohesive interface methodology, in which weak based moving connections are implemented by using a finite element formulation. The numerical formulation has been implemented by means of separate steps, concerned, at first, to identify the correct position of the crack onset and, subsequently, the growth by changing the computational geometry of the interfaces. In order to verify the accuracy and to validate the proposed methodology, comparisons with experimental and numerical results are developed. In particular, results, in terms of location and speed of the debonding front, obtained by the proposed model, are compared with the ones arising from the literature. Moreover, a parametric study in terms of geometrical characteristics of the layered structure are developed. The investigation reveals the impact of the stiffening of the reinforced strip and of adhesive thickness on the dynamic debonding mechanisms.
Keywords: Debonding; ALE; Dynamic Delamination; FEM; Crack Onset